C80 SUDDEN CARDIAC ARREST IN A YOUNG FOOTBALL PLAYER DUE TO DOCUMENTED SPONTANEOUS CORONARY ARTERY DISSECTION. (18th May 2022) - Buccheri, D; Priolo, L; Inglese, F; Barone, G
Abstract: A 28–years–old male presented with sudden cardiac arrest (SCA) while playing soccer. He was quickly resuscitated and transported to the closest cardiology department. He had no ECG or echocardiographic alterations. Coronary angiography (CA) showed a spontaneous coronary artery dissection (SCAD), confirmed by optical coherence tomography (OCT), in the mid portion of left anterior descending artery (LADA). In light of his young age, and the lack of evidence of stenosis on angiography confirmed by an instant wave–free ratio (iFR) analysis that confirmed the absence of myocardial ischemia (value obtained 0.97), the patient was treated conservatively with aspirin, clopidogrel, a statin and a beta–blocker. The patient refused implantation of a cardioverter–defibrillator repeatedly. A repeat CA was performed 6–months later, showing same findings and angiographic images of the known lesion involving the LADA. Therefore, the patient was indicated as unsuitable to play soccer. At 1 year from the index event, the patient had an episode of angina pectoris associated with intensive effort and, because of this, another CA with OCT analysis were performed. On angiography the LADA showed a significant stenosis in the same region where spontaneous dissection was previously documented; finding of hyperreflectivity on OCT suggested fibrosis of the vessel wall, probably caused by anomalous immunity reaction mimicking an autoimmune disease; residual intimal–tear representing the entry–site of the dissection was also detected, and a minimal lumen area of 2.21 mm2 was calculated consistent with angiographic stenosis. PCI was indicated, implanting a 3.0/18 mm drug–eluting stent in the mid portion of the LADA, obtaining good final angiographic result and OCT analysis confirming optimal device expansion, without residual dissection. At 2 month post–PCI the patient had returned to playing football without limitation of physical activities. 1 year post–PCI follow–up the patient is still asymptomatic and healthy. In summary, we present a case of SCAD causing an acute coronary syndrome presenting with SCA, which limited subsequent physical activity. In young patients, mostly women, SCAD episode should be strongly considered in the setting of an acute coronary syndrome. Several articles had reported that medical therapy should be oriented on the pathophysiology of SCAD due to the absence of the classic atherosclerotic burst, limiting interventional therapy when strictly indicated.